KONTRIBUSI PENERAPAN EVALUASI TEKNIK MULTIPLE CHOICE TERHADAP MOTIVASI BELAJAR SISWA DI KELAS XI IPS SMA NEGERI 1 BATANGTORU - MUHAMMAD YUSUF RITONGA (Jurnal Education and Development, 2019)
The purpose of this study is to find out whether there is a significant the effect treatment evaluation of multiple choice tecnique toward student’s learning motivation at the XI IPS grade of SMA Negeri 1 Batangtoru. The research method that was used is descriptive. The study population is all of students in class XI IPS of SMA Negeri 1 Batangtoru which consists of 3 parallel classes totaling 94 students. There are 49 students as the sample of this study which were used to random sampling, were used to called the data and used descriptive and inferential analyses. To find out the effect of the research the writer using the formula of “r” Products Moment was applied. The result of “r” Products moment shows that is greater than (0,420 > 0,282). It means there are a significant of the effect treatment evaluatin of multiple choice tecnique toward student’s learning motivation of the XI IPS grade of SMA Negeri 1 Batangtoru.